2022-RA-1579-ESGO RACE: retrospective study on rare types of cervical cancer- CEEGOG CX-06. (20th October 2022) - Dovnik, Andraž; Pakiž, Maja; Frühauf, Filip; Cibula, David
Abstract : Introduction/Background: Rare cervical tumours represent a heterogeneous group of epithelial, mesenchymal, mixed, melanocytic, lymphoid and haematopoietic, germ-cell, and even secondary tumours involving the uterine cervix. The majority of available data for these tumour types are derived from small case series where the different tumours are commonly analysed together as a larger group of rare tumours. As Central and Eastern European regions still face higher incidence rates of cervical cancer, higher numbers of rare cervical tumours are available for analysis. The aim of this multicentre international collaboration is to collect data from patients with rare tumour types diagnosed within the last 16 years, sufficient to analyse survival of individual tumour types and identify their prognostic parameters. Methodology: A retrospective cohort study involving 61 centres from 13 countries within CEEGOG has been initiated. Retrospective data on rare types of cervical cancers will be collected. The inclusion criteria are histologically proven adenocarcinoma (unusual types of mucinous adenocarcinoma: intestinal, signet ring cells, minimal deviation, villoglandular; endometrioid adenocarcinoma; clear cell adenocarcinoma; serous adenocarcinoma; mesonephric adenocarcinoma), adenosquamous carcinoma, glassy cell carcinoma, adenoid basal carcinoma, adenoid cystic carcinoma, undifferentiated carcinoma, low-grade neuroendocrine tumour, high-grade neuroendocrine tumour, leiomyosarcoma, rhabdomyosarcoma, alveolar soft part sarcoma, angiosarcoma, malignant peripheral nerve sheath tumour, other sarcomas, adenosarcoma, carcinosarcoma, malignant melanoma, lymphoma, myeloid neoplasms and secondary tumours. Furthermore, the inclusion criteria are the date of primary diagnosis between January 2005 and June 2021 with the available follow-up information. The exclusion criteria are histologically proven usual mucinous adenocarcinoma-endocervical type, HPV associated invasive adenocarcinoma and squamous cell carcinoma. Results: Conclusion: This study is aimed to differentiate the survival and prognostic factors of various rare cervical tumour types. In addition, the data from this retrospective study will serve as a basis for a prospective registry with a possibility to merge with other existing registries.